Currarino Syndrome: A Rare Case Report of Sepsis and Its Management - Theodosopoulou, Polyxeni; Micha, Georgia; Koutalas, Ioannis; Karachanidi, Stavroula; Brattou, Panagiota; Paraskeva, Anteia (Puerto Rico Health Sciences Journal, 2022)
Currarino syndrome (CS) is characterized by a triad of anomalies consisting of: a sacral bone defect, anorectal malformations and a pre-sacral mass. We present the case of an adult patient with a medical history of CS who presented with septic shock and was subjected to an emergency laparotomy due to severe abdominal distension. In this particular case, we underline the importance of immediate surgery on the patient’s outcome as well as the considerable role of landiolol in controlling the heart rate with no further deterioration of blood pressure in this patient presenting with atrial fibrillation and sepsis.